Model Kepemimpinan Integratif untuk Kewirausahaan Pendidikan Islam: Sintesis Literatur menuju Keberlanjutan Finansial: An Integrative Leadership Model for Islamic Education Entrepreneurship: A Literature Synthesis toward Financial Sustainability - Ningrum, Annisa Prawati; Nurachadijat, Kun; Heriyanto, Teguh (Risalah Kharisma, 2026)
Islamic education faces financial sustainability challenges due to limited funding and reliance on unstable donations. One potential solution is the concept of Islamic education entrepreneurship, which aims to create financial independence for educational institutions. This study aims to analyze the influence of various leadership styles on the effectiveness and sustainability of Islamic education entrepreneurship. The research employs a qualitative literature review approach, analyzing different leadership models such as transformational, participatory, spiritual, visionary, values-based, and collaborative leadership. The findings indicate that a combination of several leadership styles can enhance innovation, efficiency, and financial sustainability in Islamic educational institutions. The study concludes that effective leadership plays a crucial role in ensuring the success of Islamic education entrepreneurship. The implications of this research highlight the need for developing leadership models suited to the needs of Islamic educational institutions to address sustainability challenges optimally.